Czech Republic : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that the Czech Republic's GDP expanded by 3.1 percent in 2003 and the first quarter of 2004, mainly supported by household consumption. Investment was also strong in 2003-driven by spending on public infrastructure-and swelled in early 2004 owing to one-off influences associated with European Union accession. The fiscal deficit continued to drift upward in 2003. The general government deficit widened relative to GDP by about 1 percentage point to nearly 5 percent of GDP in 2003.